Keefektifan Konseling Kelompok dengan Teknik Thought Stopping untuk Meningkatkan Kontrol Diri Bagi Residivis di LPKA Klas I Palembang: The Effectiveness of Group Counseling with Thought Stopping Techniques to Increase Self-Control for Recidivists at LPKA Class I Palembang - Ade Nugraha ade; Suryati; Hartika Utami Putri (UIN Kiai Haji Achmad Siddiq Jember, 2023)
The player problem in this study is that there are still many levels of recidivism in LPKA Class I Palembang. LPKA Class I Palembang has a level of recidivism that pays attention, there are 22 recidivists who are still serving their prison terms, which can lead to damage to the order of life in society, so efforts are needed so that recidivists in LPKA Class I Palembang foster recidivists through group counseling with the Thought Stopping technique to increase self-control for recidivists with the aim that recidivists can stop negative thoughts and can increase their ability to control their behavior in society. The sample data collection technique was using purposive sampling technique with a total population of 22 recidivists. Analysis of the research data using the Wilcoxon test, the results obtained by filling out a 25-item questionnaire, from the Wilcoxon test results in the experimental group, Asymp.sig(2-tailed) 0.002 was obtained. value 0.002 < 0.05 and control group Asymp.sig(2-tailed) 0.027. value 0.002 < 0.05 obtained from the pretest and posttest results which means that Ha is accepted and effectively used to increase self-control for recidivists at LPKA KLAS in Palembang.